ON ANNIVERSARY: PhD Professor IOVANCA HAIDUC - OZUNU, Alexandru (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
This year marks the 15th anniversary of the establishment of the Faculty of Environmental Science and Engineering, at Babeş-Bolyai University of Cluj-Napoca. The Faculty was established in 2002 to unify in a single coherent academic structure the different forms of environmental education that had appeared since 1990 at other faculties of the Babeș-Bolyai University (Geography, Biology-Geology, Physics, Chemistry and Chemical Engineering). The Faculty of Environmental Science and Engineering promotes a modern and dynamic education in national and international context, in one of the most attractive and most important areas at present: study of the environment and environmental protection. The Faculty of Environmental Science and Engineering is the only faculty in the country offering study programs in this field, at bachelor, master and doctorate level. The educational offer of the faculty includes two major directions, namely: Environmental Science and Environmental Engineering. Mrs. Iovanca Haiduc was part of the team of founding members who initiated the establishment of the Faculty of Environmental Science, later becoming the Faculty of Environmental Science and Engineering (in 2011). The continual development of the image of the institution and mostly of the qualitative content of didactic and scientific research activities carried out within our faculty was achieved with the support of outstanding personalities of the Romanian higher education in our university, including Ms. Iovanca Haiduc, to whom we dedicate this special issue of the scientific journal Ambientum, at a time when we celebrate together the anniversary of her birthday. This homage is not one of complaisance, dictated by the double conjuncture moment mentioned above, but is based on the acknowledgement of the fact that some personalities of the academic environment of Cluj deserve not only the attention of their contemporaries but also of younger generations, representing models to follow. Professor Iovanca Haiduc is a member of this category. As a remarkable academic person and a reputed scientist, Professor Iovanca Haiduc is one of the academic personalities of higher education in chemistry and environmental science with special professional, scientific and managerial skills, who managed to put her mark on the formation of our faculty at that time. She started her academic career at Babeş-Bolyai University from 1962 until 2009. At first she was a member of the Faculty of Chemistry, and since 2002 he has strengthened the teaching staff of the newly established Faculty of Environmental Science, whose dean she was between 2002 and 2008. Throughout her career, she has carried out intensive didactic and research activities, publishing alone or in collaboration 9 books and 4 collections of problems and practical works of analytical chemistry and environmental analysis, and about 90 scientific papers (65 in the country and 25 abroad). Professor Iovanca Haiduc benefited from internships abroad at renowned universities: University of Iowa (USA), University of Nottingham (England), Lehigh University (USA), University of Singapore, which allowed her to open up her vision of research and teaching activities supported by our faculty. Her vast and complex activity with 47 years of dedication and passion devoted to the study and scientific creation, her academic pursuit, the seriousness and the conscientiousness with which she performed her mission everywhere she worked, were acknowledged and appreciated by everyone in the academic environment. We are glad that we have the opportunity to pay homage to Professor Iovanca Haiduc, to honour her properly, and to thank her for all that she has given us throughout the years in our faculty. Happy anniversary, Mrs. Professor Iovanca Haiduc! May you have happiness, fulfillment and much health!